-3+8-6t=-6t+5

Simple and best practice solution for -3+8-6t=-6t+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+8-6t=-6t+5 equation:


Simplifying
-3 + 8 + -6t = -6t + 5

Combine like terms: -3 + 8 = 5
5 + -6t = -6t + 5

Reorder the terms:
5 + -6t = 5 + -6t

Add '-5' to each side of the equation.
5 + -5 + -6t = 5 + -5 + -6t

Combine like terms: 5 + -5 = 0
0 + -6t = 5 + -5 + -6t
-6t = 5 + -5 + -6t

Combine like terms: 5 + -5 = 0
-6t = 0 + -6t
-6t = -6t

Add '6t' to each side of the equation.
-6t + 6t = -6t + 6t

Combine like terms: -6t + 6t = 0
0 = -6t + 6t

Combine like terms: -6t + 6t = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -4-3x=-10-4k | | 3a-(8-6b)= | | -8-8m=-8m-8 | | 5+3x=8x+10 | | 7-(4y-1)=2-5y | | 3-5b=7-6b | | -8p=-4p-4p | | 8.6x+1.09=21.5x+16.9 | | 3(x+8)=-36 | | 4(3x+9)=-38+62 | | 3k+8=5k-8 | | 72=16t^2+4t | | 15x+3=10x+18 | | 2(3x-4)+3=21 | | 6-9r=-9r | | 11x-53=46 | | -4-3x=-5 | | 7x+3=6+5 | | 2x-2+8x=10x+30 | | 4.2(3.1+6.4x)=17.5x-2.3 | | -10+6z=10z+10 | | -8+9u=8u | | 4x+6.3=-3.7 | | 4b+7=4b | | -6+9g=10g | | 49c^2-25d^6= | | (x+4)x(x-5)=-14 | | 3q-8=4q | | -4t=-8t-12 | | -3v=2-3v | | 20x-36*-20=-6 | | -15+7y=25+2y |

Equations solver categories